Oribatid mites (Acarina, Oribatida) from French Guyana III. A new subgenus and its type species, Sternoppia (Luisternoppia) subiasi sp. nov. from family Sternoppiidae Balogh et Mahunka, 1969 - Miko, Ladislav (Zootaxa, 2024)
The first recorded finding of a species belonging to the oribatid mite family Sternoppiidae is reported from French Guyana. Sternoppia (Luisternoppia) subgen. nov., is characterised by a developed transcostula, long notogastral setae and strongly modified epimeral setae 3a and 4a, and its type species, S. (L.) subiasi sp. nov. is described based on individuals collected from leaf litter and upper soil of the tropical rainforest in the Kaw Mountains. A subgeneric diagnosis, type species description and an identification key to the subgenera of Sternoppia are provided.